200 likes | 232 Views
Explore regular languages, expressions, and operators, learn how to form regular expressions, convert DFA to regex, and dive into laws and proofs of regular expressions in automata and formal languages.
E N D
3. Regular Expressions and Languages CIS 5513 - Automata and Formal Languages – Pei Wang
Regular languages L is a regular language if and only if it is accepted by a DFA or NFA (or ε-NFA) Regular languages can be specified without automata, but with regular expressions Regular expressions are notations that specify a language declaratively, focusing on the symbolic patterns in the sentences Expression E denotes language L(E)
Operators of regular languages A language is a set of strings, therefore • Union: The union of two languages L and M, LM, is set union of the two • Dot: The concatenation of two languages L and M, L•M or LM, is string concatenation of the two (similar to Cartesian product L×M) • Star: The closure of a language, L*, is defined as L0 L1 L2 L3 …, where L0 = {ε} andL1 = L
Operators of regular expressions Regular expressions are formed recursively • Constant or symbol: L(Ø) = Ø, L(ε) = {ε}, L(a) = {a} • Union, concatenation, and star: L(E+F) = L(E)L(F) L(EF) = L(E)L(F) L(E*)= (L(E))* • Parenthesized expression: L((E)) = L(E)
Order of precedence Order of precedence of regular-expression operators, from high to low: star > dot > union Example: Regular expression for the strings that consist of alternating 0’s and 1’s • (01)*+(10)*+0(10)*+1(01)* • (ε+1)(01)*(ε+0)
Exercises Write regular expressions for the following languages: • 3.1.1(a) The set of strings over alphabet {a,b,c} containing at least one a and at least one b • 3.1.2(a) Binary strings where every pair of adjacent 0’s appear before any pair of adjacent 1’s Solution: http://infolab.stanford.edu/~ullman/ialcsols/sol3.html#sol31
DFA to R.E. by inclusion (1) A regular expression can be built from a DFA for the same language Proof: mathematical induction on the states to be used as intermediate in DFA (1) Name the states of D from 1 to n, starting at the start state (2) Use Rij(k)for the regular expression where L(Rij(k)) = {w | w is the label of a path in D from state i to state j without going through nodes greater than k}
DFA to R.E. by inclusion (2) (3) The basis is k = 0, where Rij(0) is the union of the symbols on the direct edges from i to j (4) Given Rij(k-1) for all pairs of state Rij(k) = Rij(k-1) + Rik(k-1) (Rkk(k-1))* Rkj(k-1) (5) When k = n, the regular expression for L(D) is the union of all R1j(k)where j is a final state The above procedure works for NFA or ε-NFA, too
DFA to R.E. by elimination (1) Eliminating the state s
DFA to R.E. by elimination (2) Overall process: (1) Label the edges using r. e. (2) Repeatedly eliminating states for each final state, get a r.e. (R+SU*T)*SU* or R* (3) Take the union of all the resulting r.e.
DFA to R.E. by elimination: example Resulting R.E.: (0+1)*1(0+1)+ (0+1)*1(0+1)(0+1) or (0+1)*1(0+1)(ϵ+0+1)
Regular expression to ε-NFA (2) • Regular expression: • (0+1)*1(0+1) • 0+1 • (0+1)* • (0+1)*1(0+1) • How about a simpler one?
Regular expressions in UNIX In UNIX, regular expressions are widely used to represent patterns in text • “.” for any character • “[abc]” for a+b+c • “[a-z]” for any character between a and z • “[:digit:]” for any digit, as [0-9] • “[:alpha:]” for any letter, as [A-Za-z] • “[:alnum:]” for any digit or letter, as [A-Za-z0-9]
Regular expressions in UNIX (cont.) • Infix “|” for union • Suffix “?” for “zero or one of” • Suffix “+” for “one or more of” • Suffix “{n}” for “n copies of” Please note that the above usage is not identical to how “regular expression” is defined in our context
Laws for regular expressions Two regular expressions are equivalent if and only if they specify the same language • L + M = M + L • (L + M) + N = L + (M + N) • (LM)N = L(MN) • Ø + L = L + Ø = L • εL = Lε= L • ØL = LØ= Ø
Laws for regular expressions (cont.) • L(M + N) = LM + LN • L + L = L • (L*)* = L* • Ø* = ε • ε* = ε • L+ = LL* = L*L • L* = L+ + ε • L? = ε + L
Proving a law of regular expression To prove a law of regular expression: • Converting the regular expressions by replacing the variables by different symbols • Checking the equality of the two languages produced by the regular expressions Theorem 3.14 proves this procedure is correct using the substitutability of symbols by strings Disprove a “law”: one single instance is enough
Proving the laws: examples Check the following identities: • Exercise 3.4.1(a): R + S = S + R • Exercise 3.4.1(f): (R*)* = R* • Exercise 3.4.2(a): (R + S)* = R* + S* • Exercise 3.4.2(c): (RS + R)*RS = (RR*S)* Solution: http://infolab.stanford.edu/~ullman/ialcsols/sol3.html#sol34